PELATIHAN PERANAN KELUARGA DAN MASYARAKAT DALAM PENDIDIKAN ISLAM DI SEKOLAH - Bambang Ismaya; Resty Gustiawati; Nancy Riana (SABAJAYA Jurnal Pengabdian Kepada Masyarakat, 2023)
Learning Training and the primary source of education is family education. As every kid is born in the core of the family and receives the first education in the family, the family is considered to be the first educational institution. It is claimed largely because the education that arises and occurs in this household has a significant impact on the lives and later education of children. The function of the culture is also one of the most important in Islamic education since the kid is aware of his surroundings, both good and negative, and this environment has an influence on the role of Islamic education.